Enhancing Collaborative Learning through the Rotating Trio Exchange Model: A Systematic Literature Review on Educational Management Dimensions - Aulia Bintang; Armiati (Al-Qalam Institue, 2025)
Education plays a crucial role in shaping human resources capable of driving national progress in the 21st century. However, many educational systems in developing countries still rely on teacher-centered approaches, hindering the development of critical thinking, collaboration, and adaptability skills needed in an interconnected world. This study aims to explore the effectiveness of the Rotating Trio Exchange (RTE) cooperative learning model in improving student learning outcomes and engagement. The methodology used is a Systematic Literature Review (SLR) combined with bibliometric analysis using VOS Viewer software to examine patterns, trends, and emerging themes in RTE research. The results indicate that the RTE model is effective in enhancing student engagement, communication skills, and collaboration. This model also supports the development of 21st-century skills and addresses the challenges of modern education. The contribution of this research lies in providing empirical and theoretical foundations for the application of RTE in more inclusive and collaborative learning environments.